Non-linear radiative squeezed flow in a rotating frame. Issue 8 (6th November 2017) - Ahmed, Naveed; Khan, Umar; Mohyud-Din, Syed Tauseef; Jan, Saeed Ullah
Abstract : Purpose: In this current study, the authors aim to analyze non-linear radiative squeezed flow in a rotating frame of viscous fluid. Design/methodology/approach: The Radioactive nature of the fluid is taken into consideration. The reduced form of equations governing the flow are developed by the implementation of similarity transformations. The coupled system thus obtained is solved by using the homotopy analysis method (HAM). Findings: Augmentation in velocity and temperature profiles is discussed graphically by varying various involved parameters. The total error of the system is discussed in Table I. The cases of linear radiation and non-linear radiation are also discussed in Tables II and III. Originality/value: The study presented in this paper is original and it has not been submitted to any other journal for publication purpose. The contents are original and proper references have been provided wherever applicable.